Organizational change in a Malaysian public university / Za’faran Hassan, Ahmad Suhaimi Ismail and Roziah Mohd. Janor - Hassan, Za’faran; Ismail, Ahmad Suhaimi; Janor, Roziah Mohd. (Universiti Teknologi MARA Cawangan Pahang, 2004)
Any organization that ignores the concept of change does so at its own peril. Modern organizations have to come to terms with a number of issues that will create a need for change. What is important, however, is the recognition that change occurs continuously, has numerous causes, and needs to be addressed all the time. Overall, planned change is not impossible, but it is often difficult. But what is it that makes an organization want to change? These may include factors related to the external environment, internal changes or perhaps where the organization itself tries to be ahead of change itself by being proactive. Many attempts have been made to characterize and classify organizational change approaches, and many dimensions for comparison have been suggested in relation to this. This paper describes the experience of planned organizational change in a local university, and its experiential support for a theoretical change model.